Zolmitriptan-induced growth hormone release in humans: mediation by 5-HT1D receptors? - Whale, R; Bhagwagar, Z; Cowen, P (1999)
RATIONALE: Effective neuroendocrine probes of 5-HT1B and 5-HT1D receptor function may facilitate investigation of the role of these receptor subtypes in the pathophysiology of depression and the mode of action of antidepressant medication. OBJECTIVE: To investigate the neuroendocrine profile of the 5-HT1B/1D receptor agonist, zolmitriptan, in healthy volunteers. METHODS: Twelve subjects entered a double-blind, placebo-controlled, cross-over design study of zolmitriptan (5 mg orally). Blood samples were taken at 15-min intervals for assay of prolactin and growth hormone. A further six healthy men were recruited to an equivalent study to examine the effect of ketanserin (a 5-HT receptor antagonist with some preference for 5-HT1D over 5-HT1B receptors) on the growth hormone response to zolmitriptan. RESULTS: Zolmitriptan significantly increased plasma growth hormone but had no effect on plasma prolactin or oral temperature. The increase in growth hormone produced by zolmitriptan was significantly attenuated by ketanserin. CONCLUSIONS: We suggest that the ability of triptans such as zolmitriptan, sumatriptan and rizatriptan to increase plasma growth hormone is mediated by their common agonist activity at postsynaptic 5-HT1D receptors.